Organic cocoa extract - loaded surfactant- based systems intended to skin bioadhesion - Fonseca-Santos, Bruno [UNESP]; Funagoshi, Erica Emi [UNESP]; Soares de Oliveira, Jose Ricardo [UNESP]; Silva do Sacramento, Luis Vitor [UNESP]; Santos, Andre Gonzaga dos [UNESP]; Leonardi, Gislaine Ricci; Chorilli, Marlus [UNESP] (Univ Sao Paulo, Conjunto Quimicas, 2017)
This study was to develop, characterize, and evaluate the physical-chemical stability, in vitro antioxidant activity and in vitro safety profile of liquid crystalline systems (LCS) and microemulsions (MEs) with and without organic cocoa (OC) extract. LCS stabilized by surfactant polyoxyethylene 20 cetyl ether, containing water and oleic acid were studied. LCS and MEs were characterized using polarized light microscopy, small angle X-ray scattering, rheology and in vitro bioadhesion, and were evaluated for a period of 30 days by visual aspects, centrifuge test, pH value and relative density. PLM and SAXS assays showed the presence of domains of MEs, cubic and hexagonal mesophasephases, varying the proportions of the components of the formulations; where in the addition of the extract did not change rheological behavior of the formulations. All of the formulations were stable in the period analyzed and presented higher bioadhesive strength. In vitro antioxidant activity suggests that LCS and MEs presented a high capacity to maintain the antioxidant activity of OC extract. The results showed that the incorporation of OC in LCS improved the safety profile, according to cytotoxicity assays of systems may be a promising platform to OC extract for topical application for the potential treatment of skin disorders.
Keywords: Liquid crystals/evaluation/physical-chemical stability. Microemulsions/evaluation.; Surfactant-based system. Organic cocoa extract. Skin bioadhesion.